Enzyme linked receptor protein signaling pathway is one of the ontology groups that are highly up-regulated in porcine oocytes before in vitro maturation - Borys, S; Brązert, M; Jankowski, M; Kocherova, I; Ożegowska, K; Celichowski, P; Nawrocki, M J; Kranc, W; Bryja, A; Kulus, M; Jeseta, M; Pieńkowski, W; et al. (Journal of biological regulators and homeostatic agents, 2018)
Before being able to fully participate in the processes associated with its function as a female gamete, the oocyte needs to undergo a range of changes to achieve its mature form. These morphological, biochemical and metabolomic processes are induced by the somatic tissues surrounding the oocyte, through the expression of specific transcription and growth factors. The maturation of the oocyte is highly important for the proceedings that lead to successful fertilization, early embryonic development and implantation. Domestic pigs were used as models for our study, with the cumulus-oocyte complexes obtained from the ovaries that were recovered at slaughter. After shedding of the cumulus, oocytes were assessed with BCB test, with the viable ones chosen to undergo in vitro maturation. With the use of expression microarrays, we analyzed gene expression before and after IVM and detected major changes in both genes that were proven to be associated with oocyte maturation before (FOS, VEGFA, CHRDL1, TGFBR3, FST, INSR, ID1, TXNIP, SMAD4, MAP3K1, EIF2AK3 and KIT) and genes not previously linked with reproduction associated processes (MYO1E, PHIP, KLF10 and SHOC2). All the genes were briefly described, with consideration of possible involvement of the newly discovered elements of the transcriptome in the process of oocyte maturation.
Keywords: In Vitro Oocyte Maturation Techniques; Animals; Oocytes; transkriptom; Cumulus Cells; Female; zvířata; Transcriptome; oocyty; prasata; Swine; stanovení celkové genové exprese; signální transdukce; Gene Expression Profiling; IVM techniky; ženské pohlaví; kumulární buňky; Signal Transduction